Acalypha australis Linn,-an Addition to Indian Flora - Singh, N. P. (Indian Forester, 1967)
Acalypha australis Linn., a chinese species with a range of distribution extending to Japan, is now recorded from Dehra Dun in Uttar Pradesh, India, as a weed of tea plantations, A detailed descriptive account of the species supported by illustrations is provided in the paper.